The problem of POP pesticides in Kazakhstan and methods for their restoration using the new high-efficient phytoremediant Мiscanthus sinensis (on the example of the Talgar region) (Eurasian Journal of Ecology, 2019)
Abstract. In the article has been shown results of the monitoring the territory of the former storehouse pesticides (vil. Kyzyl-Kairat, Talgar district, Almaty region) and assessing the remediation abilitysoil contaminated with POPs (persistent organic pesticides) of the new bioenergetic species Miscanthussinensis. Established that the soil around the former warehouses contaminated with persistent organicpesticides (HCB, α-HCH, γ-HCH, β-HCH, δ-HCH, DDT, 4.4’DDE, 2.4’DDD, 4.4’DDD, aldrin, heptachlor, hexabromobenzene, heptachloroepoxide, deldrin, dibutylendan, keltan, methoxychlor, endrin,endrin aldehyde, endosulfan sulfate, endosulfan, chlordane, chlorobenzylate), the concentrations ofwhich exceeded MAC up to 120 times. The main soil contaminants were pesticides – α-HCH, β-HCH,δ-HCH, DDT, 4.4’DDE, 2.4’DDD, aldrin, deldrin, endrin, heptachloroepoxide, endosulfan 1 and chlorobenzylate. M. sinensis was grown on the contaminated soil with pesticides was found that the planthas tolerance (tolerance index 0.76) and the ability to extract up to 11 μg of DDT metabolites fromcontaminated soil. Revealed a decrease in the content of chlorophyll a and an increase of auxiliary pigments – chlorophyll b and carotenoids in the leaves, as the adaptive reaction of the photosynthetic apparatus to the action of a xenobiotic. The results obtained indicate on the adaptability of M. sinensis to high concentrations of POPs pesticides in the soil and the prospect of their use for the development ofphytoremediation technology.Key words: POPs pesticides, plant, productivity, photosynthesis, phytoremediation, soil